The Legend of Lakshmi Prasad - Twinkle Khanna (Juggernaut Books, 2016)
A gangly young girl transforms her village with a revolutionary idea. Sixty-eight-year-old Noni Appa finds herself drawn to a married man 'Why to people have to define relationships, underline each word till the paper gives way beneath', she wonders. Bablu Tripathi becomes obsessed with sanitary napkins much to his family's horror, and a young woman keeps checking the weather forecast as she meticulously plans each of her five weddings. Funny, observant and wise, this is storytelling at its most irresistible.